Functional results with active middle ear implant or semi-implantable bone conduction device in patients with comparable hearing loss. (3rd October 2022) - Spiegel, Jennifer L.; Weiss, Bernhard G.; Bertlich, Mattis; Stoycheva, Ivelina; Canis, Martin; Ihler, Friedrich
Abstract: Objective: In patients with conductive (CHL) or mixed hearing loss (MHL), hearing rehabilitation with an implantable hearing system, active middle ear implant (AMEI) or a semi-implantable bone-conduction device (SIBCD), is an option when conventional hearing aids are insufficient, or patients are unable to wear them. Design: Retrospective analysis of 20 consecutive patients (24 implants) with a comparison of demographic characteristics and audiometric results (air-bone gap = ABG, effective hearing gain = EHG, functional hearing gain = FHG, Freiburg Monosyllabic Test in quiet, Oldenburg Sentence Test in noise = OLSA). Study sample: Patients, eligible for both devices, who received either AMEI or SIBCD due to CHL or MHL. Results: Analysis showed no significant differences in post-operative functional hearing results between the group of AMEI vs. SIBCD (ABG-reduction: 31.6 ± 12.4 dB HL vs. 28.0 ± 11.8 dB HL; p = 0.702; EHG: −1.6 ± 7.7 dB HL vs. −1.2 ± 4.2 dB HL; p = 0.090; FHG: 33.4 ± 12.6 dB HL vs. 26.1 ± 11.7 dB HL; p = 0.192; Freiburg: 83.0 ± 15.6% vs. 83.6 ± 14.2%; Freiburg-improvement: 57.7 ± 26.8% vs. 68.2 ± 19.7%; p = 0.294; OLSA: −2.7 ± 3.0 SNR vs. −1.4 ± 3.6 SNR; OLSA-improvement: 2.6 ± 2.1 dB vs. 3.7 ± 2.8 dB; p = 0.323). Four patients had the AMEI explanted due to insufficient functioning and later received a SIBCD. Conclusions: Due to more challenging anatomical conditions, a surgical technique for the AMEI is more complex. However, functional results are comparable to the SIBCD. Therefore, proper patient counselling and cautious choice of the device are mandated before surgery.